Analisis Dampak Lalu Lintas Depot Pengisian Pesawat Udara (DPPU) Haluoleo Kota Kendari - Andriyani, Andriyani; Kasmaida, Kasmaida (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The Haluoleo Aircraft Filling Depot has the potential to impact traffic flow due to activities surrounding the facility, necessitating a traffic impact analysis. The objective of this research is to assess the performance of road sections and intersections affected by current conditions and projections five years post-operation, using simulations for Do Nothing and Do Something scenarios for traffic management. This study employs both qualitative and quantitative analysis methods, adhering to the PKJI 2023 guidelines. The analysis results show that the service levels for both Jl. Bandara Haluoleo and Jl. Akses DPPU Haluoleo remain excellent. Jl. Bandara Haluoleo maintains a LoS A with DJ values between 0.01 and 0.02, and a travel speed ranging from 57.74 to 60.54 km/h, while Jl. Akses DPPU Haluoleo also has a LoS A and a DJ value of 0.00, with a travel speed between 58.80 and 60.97 km/h, both for the existing 2024 conditions and the 2029 projection. Road performance at the Jl. Bandara Haluoleo – Jl. Akses DPPU Haluoleo intersection shows a LoS A with DJ values of 0.01 – 0.02, and a delay time between 3.20 to 3.86 seconds/pcu